Judgement and salvation : the composition and redaction of Micah 2-5 - Wagenaar, Jan A. (Supplements to Vetus Testamentum, 2001)
This volume deals with the redaction history of the Book of Micah vis-à-vis the alternation of the oracles of judgement and the oracles of salvation in chapters 2-5. The first part of the book offers a brief discussion of the most important hypotheses to account for the alternation of doom and hope that have been put forward over the last three or four decades: the composition model, the dialogue model and the redaction-historical model. The second part of the book offers a detailed study of the text of Micah 2-5 followed by a thorough analysis of the form and literary development of the individual pericopes. The study is concluded by a fresh presentation of the redaction history of the Book of Micah.